(untitled) (Bangladesh Journal of Botany, 2022)
Morpho-anatomy of five Kalanchoe species including firstly reported Kalanchoe gastonis-bonnieri and Kalanchoe delagoensis species found in Bangladesh was analyzed to elucidate the previous taxonomic dispute by comparative study. Stomata observed in leaves of all of the experimented species were amphistomatic in nature. Presence of unequal subsidiary cells surrounding the guard cells was the cellular morphology of all the stomata. The abaxial surface of leaves contained more stomata than the adaxial surface in each species. K. gastonis- bonnieri and K. delagoensis were found to have the highest (53.4 ± 1.88 stomata/mm2) and the lowest (14.81 ± 0.53 stomata/mm2) stomatal density respectively. Many dissimilarities were observed during the anatomical study of leaves and stems. The leaf epidermis of the examined species was lack of multicellular hair and mesophyll tissue was not differentiated into palisade and spongy parenchyma. Crescent shaped vascular bundles were surrounded in the midrib regions of leaves in all species examined except Kalanchoe blossfediana. Existence of collenchymatous sheath around the midribs vascular bundles and absence of storage cells were characteristics of leaves midribs. Thick cuticular layer on the epidermis except Kalanchoe pinnata, a well-developed broad cortex except K. delagoensis and well defined pith were found to be characteristic of stem along with lack of cortical resin canal and storage cells in medullary rays. Bangladesh J. Bot. 51(2): 229-235, 2022 (June)